Physiology of Distinct Modes of Muscular Contraction - Nasim Habibzadeh (International Physiology Journal, 2018)
Physiological changes in musculature allow widespread movements in human body. Correspondingly, varying in muscle prototypes characterise direct different training paradigms in therapeutics practice or can governs athletic performances. Mode of muscle contraction type are isometric, concentric or eccentric. Great examples of concentric exercise are walking- up-hill, stair ascent and lifting a dumbbell in bicep curl or pushing a bar up. Examples of eccentric muscle actions are walking - down-hill, satire decent and, isokinetic arm and leg extensions. During isometric muscle contraction the length of muscle does not change while muscle exert force .This type of movement can be seen while a person performs a maximal voluntary contractions (MVCs).Eccentric exercises increasing the concentric and isometric contraction as well. Performing the eccentric muscle contraction in daily life enhance quality of life and lifespan due to increasing muscle strength with low cost of energy consuming and thus it can apply in variety of domains. A simple walking task such as downhill - walking (i.e. 30 min) can provide the aforementioned conditions.
Keywords: Muscle physiology